2021
DOI: 10.3389/fmicb.2021.570908
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Deposition Reduces the Diversity and Abundance of cbbL Gene-Containing CO2-Fixing Microorganisms in the Soil of the Stipa baicalensis Steppe

Abstract: CO2 fixation by autotrophic microbes has a significant effect on the carbon cycle in temperate grasslands. Nitrogen (N) deposition in soil has been steadily increasing for decades, which has consequences for soil microorganisms. However, the impact of this deposition on the diversity and abundance of CO2-fixing soil microorganisms remains unclear in temperate grasslands. In the present study, the cbbL gene, a key gene in the Calvin–Benson–Bassham cycle that encodes the large subunit of ribulose-1,5-bisphosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
(77 reference statements)
3
11
0
Order By: Relevance
“…Our results, therefore, point to the potential effects of N deposition on soil carbon stocks and CO 2 fluxes via affecting the soil microbiome (Averill et al, 2018;Z. Li et al, 2021;Qin et al, 2021). Our results are in agreement with Zhang et al (2022), who reported increasing abundances of C fixation and methane metabolism genes under N addition in a subtropical forest.…”
Section: Implications For Carbon and Nutrient Cyclingsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results, therefore, point to the potential effects of N deposition on soil carbon stocks and CO 2 fluxes via affecting the soil microbiome (Averill et al, 2018;Z. Li et al, 2021;Qin et al, 2021). Our results are in agreement with Zhang et al (2022), who reported increasing abundances of C fixation and methane metabolism genes under N addition in a subtropical forest.…”
Section: Implications For Carbon and Nutrient Cyclingsupporting
confidence: 91%
“…We conclude that the indirect effects of N deposition through soil acidification on functional gene diversity and composition are stronger than its direct effects. Such indirect effects have been previously reported for a group of genes involved in C cycling (Qin et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microbial β-diversity index was 1 http://ccb.jhu.edu/software/FLASH/ 2 http://qiime.org/scripts/split_libraries_fastq.html 3 http://www.drive5.com/uparse/ 4 http://www.arb-silva.de/ 5 http://qiime.org/scripts/assign_taxonomy.html 6 https://unite.ut.ee/ calculated using the QIIME software (version 1.9.1), and pairwise differences were further compared based on the Wilcoxon rank sum test. A LEfSe analysis (LDA score ≥ 2.0) was used to determine the significant differences in microbial community from the phylum to the genus levels using the LEfSe software (version 1.0; Qin et al, 2021). The soil properties as explanatory variables and the dominant microbial phyla as species variables were used to perform a redundancy analysis (RDA) with the vegan packages in the R software (version 2.15.3).…”
Section: Discussionmentioning
confidence: 99%